Anchoring and Catalytic Effects of rGO Supported VS2 Nanosheets Enable High‐Performance Li–Organosulfur Battery. Issue 17 (4th January 2023) - Zhang, Ping; Fu, Yongzhu; Guo, Wei
Abstract: As a high‐energy‐density cathode material, organosulfur has great potential for lithium batteries. However, their practical application is plagued by electronic/ionic insulation and sluggish redox kinetics. Hence,  our strategy is to design a self‐weaving, freestanding host material by introducing reduced graphene oxide–supported VS2 nanosheets (VS2 ‐rGO) and carbon nanotubes (CNTs) for lithium–phenyl tetrasulfide (Li–PTS) batteries. Unique host materials not only provide physicochemical confinement of active materials to boost the utilization but also catalyze the conversion of active materials to accelerate redox kinetics. Therefore, Li–PTS cell based on the 3D VS2 ‐rGO‐CNTs (VSGC) host material shows excellent cyclability, with a slow capacity decay rate of 0.08% per cycle over 500 cycles at 0.5 C, and a high areal capacity of 3.1 mAh cm −2 with the PTS loading of 7.2 mg cm −2 . More importantly, the potential for practical applications is highlighted by the flexible pouch cell with a high areal capacity (4.1 mAh cm −2 ) and a low electrolyte/PTS ratio (3.5 µL mg −1 ). This work sheds light on elevating the electrochemical performance of Li–organosulfur batteries through the effective catalytic and adsorbed host material. Abstract : The 3D conductive host material VS2 ‐rGO‐CNTs consisting of reduced graphene oxide–supported VS2 nanosheets and carbon nanotubes can physically confine phenyl tetrasulfide and facilitate its electrochemical conversion in lithium batteries, showing a capacity decay rate of 0.08% per cycle for 500 cycles.